Fermentation of Sugar Beet Pulp by E. coli for Enhanced Biohydrogen and Biomass Production - Gayane Mikoyan; Liana Vanyan; Akerke Toleugazykyzy; Roza Bekbayeva; Kamila Baichiyeva; Kairat Bekbayev; Karen Trchounian (Energies)
This study investigates the potential of sugar beet pulp (SBP), a lignocellulosic by-product of sugar production, as a low-cost substrate for biohydrogen and biomass generation using Escherichia coli under dark fermentation conditions. Two strains—BW25113 wild-type and a genetically engineered septuple mutant—were employed. SBP was pretreated via thermochemical hydrolysis, and the effects of substrate concentration, dilution, and glycerol supplementation were evaluated. Hydrogen production was highly dependent on substrate dilution and nutrient balance. The septuple mutant achieved the highest H2 yield in 30 g L−1 SBP hydrolysate (0.75% sulfuric acid) at 5× dilution with glycerol, reaching 12.06 mmol H2 (g sugar)−1 and 0.28 mmol H2 (g waste)−1, while the wild type under the same conditions yielded 3.78 mmol H2 (g sugar)−1 and 0.25 mmol H2 (g waste)−1. In contrast, undiluted hydrolysates favored biomass accumulation over H2 production, with the highest biomass yield (0.3 g CDW L−1) obtained using the septuple mutant in 30 g L−1 SBP hydrolysate without glycerol. These findings highlight the potential of genetically optimized E. coli and optimized hydrolysate conditions to enhance the valorization of agro-industrial waste, supporting future advances in sustainable hydrogen bioeconomy and integrated waste biorefineries.